Promosi Kesehatan Nola Pender Berpengaruh Terhadap Pengetahuan dan Kepatuhan ODHA Minum ARV - Tuti Asrianti Utami (Alma Ata University Press, 2017)
The success rate of ARV therapy depends on the adherence of HIV-AIDS patients in ARV treatment. The purpose of this study was to analyze the effect of NolaPender health promotion to improve the knowledge and adherence of PLWHA (People living with HIV-AIDS) with ARV in SintCarolus Health Service (SCHS) and Persahabatan General Hospital (PGH). This study used a Pre-Post test Quasi Eksperimantal Non Equivalent Control Group and a total sample of 90 respondents were recruited through the use of consecutive sampling with inclusion criteria where 45 respondents served as intervention group in SCHS and the remaining as control group in PGH from May-June 2016. The result showed most respondents were in the late adulthood stage (36-55 years old), male, having advanced education, working, exposed to counseling service, having family support as well as peer group support, easy in reaching health service and with health insurance. NolaPender health promotion increased the knowledge of ARV (mean score pre intervention was 5.31 to post intervention 7.04), and improving the adherence of taking ARV from moderate to good adherence as many as 51.1%. There was an effect of Nola Pender health promotion using booklet to respondents’ knowledge (p-value=0.000) from 13.3% to 91.1% and also effect of knowledge improvement of ARV to the adherence of taking ARV, with the support from peer group from 30.2% to 87.2%. The study recommends to continue this program of Nola Pender health promotion for PLWHA taking ARV in a structured and well planned system.